The One and Only Music for the Danish Lanciers: Time, space, and the method of East European ethnochoreologists - Damsholt, Inger (Danish Yearbook of Musicology, 2009)
The article presents a choreomusical analysis of the Danish Lanciers. In Denmark, the dance is considered closely bound to a specifi c composition by J. Mikel: the 3eme Quadrille des Lanciers – not the original music for Hart’s Lancers. The method for Dance Form Analysis, proposed by East European ICTM Ethnochoreologists, is applied to show how, and according to which parameters, the dance music is linked to the dance. The analysis shows that dance and music generally coincide and that their relationship is fi xed and constant in terms of conjunction. But it also reveals that the relationship between dance and music only is partially congruent in terms of dimension and of the inner organization. Despite the overall congruence on the highest structural levels the choreomusical relationship is completely non-congruent on the motif level.